BUILDING ECOLOGICAL INTELLIGENCE THROUGH INDONESIAN LANGUAGE LEARNING BASED ON KETHEK OGLENG DANCE - Hendriyanto, Agoes; Mustofa, Arif; Sutopo, Bakti (International Journal of Education, 2018)
Kethek Ogleng is a unique factor that shapes the aesthetics of language learning. Unfortunately, the relation between Kethek Ogleng and language learning draws only a little attention. To reveal the phenomenon, the present qualitative descriptive study was performed by investigating Indonesian language learning based on Kethek Ogleng dance. The study was conducted in SMPN (State Junior High School) 3 Nawangan, to the second semester ninth grade students of the 2017/2018 academic year. The research findings reveal that the approach can build the level of ecological intelligence of the students. Based on the responses to the questionnaire distributed, the average level of ecological intelligence and environmental skills of the students shows signs of progress. The data indicate that the mean score was 3.2 and the percentage of ecological intelligence was 65%, indicating the attainment of knowledge and skills of school and home environment preservation. The indicators of the success of this approach can be seen in the changes of attitude and behavior of students in environmental management, covering clean and healthy classrooms and toilets, the use of recyclable materials, water and electricity conservation in the classroom, protection of trees and plants around the classrooms, proper treatment of trash, and organic and inorganic waste utilization.